Fiscal Decentralization Revisited: Rethinking Local Tax Performance and Fiscal Autonomy for Fiscal Resilience - Anggi Mega Rizki; Rindu Rika Gamayuni; Pigo Nauli (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Changes in intergovernmental fiscal transfer policies and the increasing emphasis on spending efficiency in Indonesia have encouraged regional governments to strengthen fiscal independence through the optimization of locally generated revenues, particularly local taxes. This study aims to evaluate local tax performance as a strategic instrument for supporting regional fiscal autonomy and fiscal resilience under fiscal decentralization. The analysis focuses on regional governments in Lampung Province during Fiscal Years 2019–2023. Using a descriptive quantitative research design, this study employs secondary data obtained from audited regional financial reports. The analytical framework applies a value for money approach to assess local tax effectiveness, complemented by growth ratio analysis to examine revenue dynamics over time. The findings indicate that local tax performance varies considerably across regions, revenue growth remains volatile, and fiscal resilience is more likely to emerge in regions where effectiveness and growth are relatively balanced. Overall, the results suggest that strengthening fiscal autonomy requires not only achieving revenue targets but also ensuring stable and sustainable local tax performance.